An interdisciplinary educational trial for adolescent health and development in urbanising China. Issue 5 (11th June 2012) - Zang, Yu‐Li; Liu, Qian; Pu, Lin‐Zhe
<x xml:space="preserve">Abstract</x> Aims and objectives. To evaluate the effects on master student participants of an intensive interdisciplinary educational programme aiming at improving adolescent health and development services in urbanising China. Background. There is a need for interdisciplinary education and collaborative practice in health, but few educational programmes have been reported. Design. Experimental design including a qualitative component. Methods. Purposive sampling was used to identify master students in relevant disciplinary areas for the four‐day classroom learning, four‐day field learning and a half‐day reflection, focusing on key aspects of adolescent health and development in the face of rapid urbanisation. Data about family function, cognitive development, adolescent health and development competency, and difficulties caused by health conditions were collected using quantitative and qualitative methods. Result. Master student participants reported positive outcomes in adolescent health and development competency, and cognitive development. Six themes were identified about the programme and its impact: 'programme evaluation', 'programme characteristics', 'changed views about nursing and nurses', 'lessons learned', 'participation benefits' and 'suggestions for future action'. Conclusion. Interdisciplinary educational programmes are possible and beneficial at masters level but may be very challenging given the need for administrative, financial and human resources. Relevance to clinical practice. Interdisciplinary educational programmes require to start with small health sector trials to accumulate evidence and skills. Faculty development is a prerequisite for such programmes towards collaborative practice.